2022
DOI: 10.1111/fwb.13895
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fatty acid profiles shape crayfish biosynthesis and performance: Implications for riverine food webs

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 92 publications
(90 reference statements)
0
2
2
Order By: Relevance
“…These values are higher than those reported for concentrations among lipids in detritus (4.9% and 1.2%, respectively; McInerney et al, 2022) and suggest that despite a lack of some LC PUFA, our study biofilms may still represent a nutritional food resource for animals. For example, McInerney et al (2022) identified that POA and OA were among four fatty acids selectively retained by crayfish, implying that proportions of these fatty acids may be particularly important for their somatic growth.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…These values are higher than those reported for concentrations among lipids in detritus (4.9% and 1.2%, respectively; McInerney et al, 2022) and suggest that despite a lack of some LC PUFA, our study biofilms may still represent a nutritional food resource for animals. For example, McInerney et al (2022) identified that POA and OA were among four fatty acids selectively retained by crayfish, implying that proportions of these fatty acids may be particularly important for their somatic growth.…”
Section: Discussioncontrasting
confidence: 83%
“…The consistency of fungal presence was reflected in fatty acid profiles, with monounsaturated fatty acid fungal biomarkers 18:1ω9 (OA) and 16:1ω7 (POA) contributing 8%–10% and 1.5%–3.5%, respectively, to total lipids for the duration of the study. These values are higher than those reported for concentrations among lipids in detritus (4.9% and 1.2%, respectively; McInerney et al, 2022) and suggest that despite a lack of some LC PUFA, our study biofilms may still represent a nutritional food resource for animals. For example, McInerney et al (2022) identified that POA and OA were among four fatty acids selectively retained by crayfish, implying that proportions of these fatty acids may be particularly important for their somatic growth.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations